Sexual Stigma, Criminalization, Investment, and Access to HIV Services Among Men Who Have Sex with Men Worldwide. - Arreola, Sonya; Santos, Glenn-Milo; Beck, Jack; Sundararaj, Mohan; Wilson, Patrick A; Hebert, Pato; Makofane, Keletso; Do, Tri D; Ayala, George (AIDS and behavior, 2014)
Globally, HIV disproportionately affects men who have sex with men (MSM). This study explored associations between access to HIV services and (1) individual-level perceived sexual stigma; (2) country-level criminalization of homosexuality; and (3) country-level investment in HIV services for MSM. 3,340 MSM completed an online survey assessing access to HIV services. MSM from over 115 countries were categorized according to criminalization of homosexuality policy and investment in HIV services targeting MSM. Lower access to condoms, lubricants, and HIV testing were each associated with greater perceived sexual stigma, existence of homosexuality criminalization policies, and less investment in HIV services. Lower access to HIV treatment was associated with greater perceived sexual stigma and criminalization. Criminalization of homosexuality and low investment in HIV services were both associated with greater perceived sexual stigma. Efforts to prevent and treat HIV among MSM should be coupled with structural interventions to reduce stigma, overturn homosexuality criminalization policies, and increase investment in MSM-specific HIV services.